STRATEGI CASE MANAGER DALAM MENGELOLA KASUS PASIEN RAWAT INAP DI RS B KEDIRI - Widyasih Sunaringtyas* Madya Sulisno** (Universitas Muhammadiyah Jember, 2016)
Case manager is new professional in the hospital that hospital has notowned in East Java. Case manager role is to handle patient with high risk case,chronic disease that high cost possibility, complex case or complicated. Problem ofthis research focused on case manager experience in managing inpatient case. Thepurpose of this research to analyzes case manager strategy in managing inpatientcase in B. Hospital. This study was a qualitative research design with descriptivephenomenology approach took 5 main informans and 3 triangulation informansused Purpossive Sampling Technique. Data collects with indepth interview, whileat bencmarking place obtained from case manager statement through lecture anddiscussion. Data analyze use collaizi methods.Themes found from this researchsuch as : communication strategy, integration, coordination, advocacy, negotiationand empowerment. Strategy that used at bencmarking location after analyzed fromcase manager statements there are also 5 themes such as: integration,coordination, advocacy, communication, negotiation, empowerment. The casemanager experience in managing patient case influenced knowledge,communication skill and clinic skill.